Embedded systems circuits and programming - Sánchez, Julio (CRC Press, 2012)
During the development of an engineered product, developers often need to create an embedded system--a prototype--that demonstrates the operation/function of the device and proves its viability. Offering practical tools for the development and prototyping phases, Embedded Systems Circuits and Programming provides a tutorial on microcontroller programming and the basics of embedded design. The book focuses on several development tools and resources: Standard and off-the-shelf components, such as input/output devices, integrated circuits, motors, and programmable microcontrollers The implementat.